Knowledge, Attitude, and Practices of Abaca Craft Producers: Philippine Illustrations - Ermie Lux L. Matildo (Universidade Estadual de Alagoas, 2023)
The study determined the knowledge, attitude, and practices of abaca craft producers in Marihatag, Surigao del Sur. Specifically, the study sought to determine the socio-demographic profile and the knowledge, attitude, and practices in abaca craft production of the respondents. This study used a quantitative and qualitative research design, utilizing a set of questionnaires and an interview guide involving 134 abaca craft producers, who were selected through a random sampling method. The abaca craft producers were also interviewed through focus group discussion. The results indicated that respondents are 41 or older (41.8%), female (78.4%), have finished secondary level education (55.2%), have 5 to 6 dependents (38.06%), are married (70.9%), have been an abaca craft producer for less than a year (41.4%), and have attended 1 to 2 trainings (46.27%) on abaca craft production. It was found that the level of knowledge, attitude, and practices still needs improvement, with mean values of 3.46, 3.62, and 3.70, respectively. The intervention tools, therefore, should be developed to enhance knowledge, attitudes, and practices, particularly product development training and marketing support, due to the limited market area and the need to adapt to modern methods of marketing. It also identified the lack of funding for equipment and transportation vehicles, where the need to collaborate with local government units and other agencies is recommended. A proposal for a product development project for abaca craft producers is hereby recommended.